2012
DOI: 10.1055/s-0031-1298019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aldosterone Production Among Human Adrenocortical Cell Lines

Abstract: Background Several human adrenocortical cell lines have been used as model systems for aldosterone production. However, these cell lines have not been directly compared with each other. Methods Human adrenal cell lines SW13, CAR47, the NCI-H295 and its sub-strains and sub-clones were compared with regard to aldosterone production and aldosterone synthase (CYP11B2) expression. Culture media was collected 48 h after incubation, aldosterone secretion was measured and the data were normalized to the amount of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Human adrenocortical carcinoma H295R cells (ATCC, Manassas, VA, USA) and its clone HAC15 (kindly provided by Dr W Rainey, Medical College of Georgia, GA, USA; described in Wang et al (2012)) were cultured in 75 cm 2 flasks (Corning Costar, Schiphol-Oost, The Netherlands) in D-MEM/F12 (GIBCO Biocult Europe, Invitrogen) containing 5% FCS, L-glutamine, and penicillin 10 5 U/l (Bristol-Myers Squibb, Woerden, The Netherlands) at 37 8C in a 5% CO 2 incubator. Once a week, the medium was refreshed and cells of both cell lines were harvested with trypsin (0 .…”
Section: Cell Culturementioning
confidence: 99%
“…Human adrenocortical carcinoma H295R cells (ATCC, Manassas, VA, USA) and its clone HAC15 (kindly provided by Dr W Rainey, Medical College of Georgia, GA, USA; described in Wang et al (2012)) were cultured in 75 cm 2 flasks (Corning Costar, Schiphol-Oost, The Netherlands) in D-MEM/F12 (GIBCO Biocult Europe, Invitrogen) containing 5% FCS, L-glutamine, and penicillin 10 5 U/l (Bristol-Myers Squibb, Woerden, The Netherlands) at 37 8C in a 5% CO 2 incubator. Once a week, the medium was refreshed and cells of both cell lines were harvested with trypsin (0 .…”
Section: Cell Culturementioning
confidence: 99%
“…qRT-PCR analysis showed that the NCI-H295 cell line had higher expression levels of CYP11B2. In the NCI-295 cell line, mRNA expression of CYP11B2 was almost two-fold compared to that was observed in the HAC 15 cell line [54]. However, aldosterone production was lower than in other cell lines, including the HAC 15 cell line, because of the lower expression of HSD3B2 observed in the NCI-H295 cell line [54].…”
Section: Hac15 Cell Linementioning
confidence: 72%
“…Wang et al compared CYP11B2 mRNA levels and aldosterone production in human adrenocortical cell lines [54]. qRT-PCR analysis showed that the NCI-H295 cell line had higher expression levels of CYP11B2.…”
Section: Hac15 Cell Linementioning
confidence: 99%
“…To assess effects of CACNA1H WT and CACNA1H M1594V on aldosterone production, we transfected HAC15 cells, a subclone of NCI-H295R that has previously been used to assess the effect of mutant channels on aldosterone production (15)(16)(17)(18). Cells were serumstarved, and aldosterone levels were measured in the supernatant by ELISA (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%